FAKTOR – FAKTOR YANG MENENTUKAN KEPUTUSAN PEMBELIAN KENDARAAN DARI LUAR DAERAH DI KABUPATEN MIMIKA - Raymandus R. Sahelangi; Seheril S. Pongsirante (Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this study was to identify the factors that determine the decision to purchase vehicles from outside the region in Mimika Regency. This study is a descriptive study using a quantitative approach. Based on the results of the analysis, it is known that there are three factors that are formed, namely price, brand image and availability. The most dominant factor is price, followed by brand image and the last is availability.